1998
DOI: 10.1007/s11630-998-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of the three-dimensional flow in a large deflection turbine cascade with tip clearance

Abstract: Results obtained from an experimental study of the three-dimensional flow survey within and exit of a large deflection linear turbine cascade are presented for a tip clearance levels of 0.08, 1.5, 3.0 percent of chord and compared with the help of boundary layer probes and that within and exit of a blade passage was done with a miniaturised five hole probe. End wall and blade tip surface static pressures were also obtained, in addition to flow visualisation studies. A strong horse-shoe vortex forms in front of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Streamlines crossing the tip gap through the low static pressure zone inside the tip have highest leakage velocity. This figure admits that tip leakage flow is fully 3D in nature, which is neither normal to the camber line [8] nor parallel to the rotation (tangential). They flow approximately tangentially near the blade TE, where the pressure differentials between PS and SS are the lowest on the chord.…”
Section: Tip Leakage Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…Streamlines crossing the tip gap through the low static pressure zone inside the tip have highest leakage velocity. This figure admits that tip leakage flow is fully 3D in nature, which is neither normal to the camber line [8] nor parallel to the rotation (tangential). They flow approximately tangentially near the blade TE, where the pressure differentials between PS and SS are the lowest on the chord.…”
Section: Tip Leakage Phenomenamentioning
confidence: 99%
“…They interpreted the flow downstream of venacontracta of the separation bubble as a sudden expansion in flow area, with a consequent loss in total pressure being experienced by the fluid in passing through the tip clearance. However, Govardhan et al [8] observed incomplete mixing inside the tip gap (t/τ = 10) in a high loaded turbine cascade with a significant loss occurring within the tip gap. Mixing within the tiny tip gap is conclusively a source of loss due to entropy generation and loss in fraction of total pressure, which is typically observed to occur with a t/τ ratio exceeding 6.…”
mentioning
confidence: 99%